2012
DOI: 10.1517/14656566.2013.752816
|View full text |Cite
|
Sign up to set email alerts
|

Functional constipation in childhood: current pharmacotherapy and future perspectives

Abstract: Despite the widespread use of laxatives, there is a paucity of evidence to support this practice. No strong conclusions can be drawn on which laxative to prefer over the other. However, polyethylene glycol appears to be a reasonable first choice for maintenance therapy. Due to advances in our understanding of intestinal (patho)physiology, new classes of drugs have been developed. Data from adult studies are promising; however, pediatric data are lacking. Ongoing and future studies have to determine the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 100 publications
1
38
0
1
Order By: Relevance
“…Multiple laxatives have been routinely used in the treatment of childhood constipation with a number of new agents currently being trialed, mostly in adults 51 . At the present time published evidence suggests that polyethylene glycol 3350 should be the laxative of first choice in pediatrics for functional constipation 42 58 .…”
Section: Treatmentmentioning
confidence: 99%
“…Multiple laxatives have been routinely used in the treatment of childhood constipation with a number of new agents currently being trialed, mostly in adults 51 . At the present time published evidence suggests that polyethylene glycol 3350 should be the laxative of first choice in pediatrics for functional constipation 42 58 .…”
Section: Treatmentmentioning
confidence: 99%
“…Different osmotic laxatives are available, but PEG (macrogol) is the fi rst choice osmotic laxative in children with FC based on its effectiveness and safety profi le [ 37 ]. Two other commonly used osmotic laxatives are lactulose and lactitol, both synthetic derivatives of lactose, which are fermented into hyperosmolar low molecular weight acids by intraluminal bacteria [ 80 ]. Even in young children (less than 2 years of age) the use of PEG has been proven to be effective and safe [ 74 -79 ].…”
Section: Pharmacological Agents Osmotic Laxativesmentioning
confidence: 99%
“…42.3 ). These agents are also metabolized into their pharmacologically active metabolite by intestinal bacteria [ 80 ] and the metabolites stimulate colonic motility and the secretion of water and electrolytes, while they inhibit the absorption of water and electrolytes from the colon. In the colon, these nonabsorbable agents are hydrolyzed to their active metabolites, which exert a local prokinetic effect and stimulate intestinal fl uid secretion [ 80 ].…”
Section: Stimulant Laxativesmentioning
confidence: 99%
“…Constipation negatively impacts quality of life and is associated with a significant economic burden to the patients and society. The annual health care cost for CIC was around $7,500 per patient in United States (Liem et al, 2009; Sanchez and Bercik, 2011; Hoekman and Benninga, 2013; Chu et al, 2014). In China, expenditure for over-the-counter (OTC) laxatives is over 8 billion RMB per year (Chu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Linaclotide, a guanylate cyclase type C (GC-C) receptor agonist, stimulates CFTR-mediated Cl − secretion via elevation of intracellular cGMP level (Tien et al, 1994). Linaclotide can also increase intestinal motility through activation of colonic sensory and motor neurons (Hoekman and Benninga, 2013; Chu et al, 2014). Lubiprostone, a prostaglandin E (PGE) analog, was once regarded to activate type-2 chloride channel (ClC-2)-mediated Cl − secretion in enterocytes, but subsequent studies indicated that lubiprostone activated CFTR chloride channel through E-type prostanoid 4 (EP4) receptors (Norimatsu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%